LANGUAGE PRODUCTION OF A SCHIZOPHRENIC CHARACTER IN THE SOLOIST MOVIE - PUSPITASARI, ELISHA CENDY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Puspitasari, Elisha Cendy. 2014. Language Production of Schizophrenic Character in The Soloist Movie. Study Program of English, Universitas Brawijaya. Supervisor: Fatimah, Co-supervisor: Eni Maharsi.Keywords: Psycholinguistics, Language Production, Schizophrenia, The SoloistMovieThis research is about Schizophrenic’s language production produced by the main character in The Soloist Movie. The schizophrenia is chosen as object because this disease is very unique and rare. The uniqueness of this case is on its symptoms where schizophrenics look like normal people but when they start to talk, the addressee will figure out the abnormality on their language production.There are two problems to be solved in the study, namely (1) to what extent does Nathaniel Anthony Ayyers as the character afflicted with schizophrenia produce his language? and (2) What are the situations which trigger abnormality in language production of Nathaniel Anthony Ayyers?.This study employs qualitative method since the data were processed without using numbers. The data were taken from transcript of movie for the purpose of identifying the language production of the schizophrenic, describing the abnormality in the language of schizophrenic, and identifying situations in which Nathaniel Anthony Ayyers shows his abnormality in his language. In the data analysis, Kraeplin (1887) theory about types and symptoms of schizophrenia was used to analyze the utterance produced by the schizophrenic character in The Soloist movie.Result of analysis reveals that there are 11 scenes in which typical language production of schizophrenia occurs. Scenes 2, 7, 15, 17, and 18 show the Ignorant and Fast Talking, and scenes 7, 10, and 14 shows the Irrelevant Respond. There are three situations trigger the occurrence of the abnormality ofschizophrenic in producing his language. The situations are triggered by anger,nervousness, and also interest. Two scenes show the situation triggered by anger (scenes 17 and 20), 3 scenes depict the situation triggered by nervousness (scenes 16, 17 and 19), and the last is 5 scenes which show that the situation triggered by interest, (scenes 2, 7, 9, 13, and 18).Conclusion of this study is Nathaniel as a schizophrenic mostly could not talk normally. Abnormality mostly appears whenever he heard music. The future researchers or other psycholinguists who concern in exploring schizophrenia phenomena are suggested to explore and look into some other categories of schizophrenia in other media in order to find some other triggers.